Pengaruh Pemberian Insentif terhadap Motivasi Pegawai Distrik Teminabuan Kabupaten Sorong Selatan - Mayaut, Godlief Satrianto; Clan, Edward; Maryen, Andrei (CV. Creative Tugu Pena, 2022)
The problem in this study is whether the provision of incentive have a significant effect on the work motivation of district employees teminabuan south sorong regency.the aim of this research is to determine whether there is an effect of providing incentives on employee motivation.the type of research used is quantitative with an associative approach.data collection techniques conducted observation questionnaires and documentation.while the data analysis technique used is simple linear regression.as for the type of data source,this research is primary data,namely data obtained directly from the source or place where the research is carried out.the population of this study were all employees of the teminabuan district amounting to 45 people.the determination of the sample is saturated sampling. Data obtained using SPSSv 24 (Statistical product and Service Solutions).the result of this study indicate that based on the result of your research at the teminabuan district office thet the provision of incentives has a significant effect on employee work motivation.this can be seen from the result of statistical calculations through partial hypothesis testing which shows that t count> t table then Ha is accepted and Ho is rejected. Keywords: Effect of Incentives, Work Motivation, Incentives